Convergence continuum of the mass media Riau Pos - Lestari, Yayuk; Yazid, Tantri Puspita; Al Dillah, Ramadhani Indah; Elsarena, Mai Sela Rosa (Jurnal Kajian Komunikasi, 2023)
Background: The flow of globalization and the rise of the Internet have forced the mass media to come to terms with these changes and go hand in hand to survive. Riau Pos, the oldest mass media in Riau Province has become the first print media in Riau to practice convergence by establishing an online news portal now named RiauPos.co. Purpose: This study aims to analyze the convergence continuum of the mass media Riau Pos on the five Continuum Convergence processes. Methods: This study uses a qualitative method with the Continuum Convergence theory published by Daily, Demo, Spillman, and the concept of Management. Results: The result revealed that Riau Pos carried out all stages of Continuum Convergence such as Cross Promotion, Cloning, Coopetition, and Content which are done simultaneously with media within the Riau Pos Group. The basis of the implementation of this convergence is a collaboration that emphasizes the characteristics of each platform. Conclusions: Full convergence has finally been finally implemented, although not yet perfect, in the implementation of 3M, namely Multichannel, Multimedia, and Multiplatform. Implications: Implementing this convergence is indeed a way for Riau Pos to survive as a print media in the form of newspapers and cyber media through its website, RiauPos.co.